Management of cases suffering from atypical myopathy: Interpretations of descriptive, epidemiological and pathophysiological findings. Part 2: Muscular, urinary, respiratory and hepatic care, and inflammatory/infectious status. (19th July 2012) - van, G.; Votion, D.‐M.
Summary Atypical myopathy is highly fatal, but about a quarter of affected horses survive. This highlights the need for provision of supportive treatment for these patients. This review is a practical guideline for equine practitioners and includes suggestions for close monitoring of involved organ systems and discusses options of supportive treatment based on current knowledge of the condition. Part 2 covers the muscular, urinary, respiratory and hepatic systems, and the general inflammatory/infectious status of the case.